Mechanistic kinetic modeling for catalytic conversion of DME to gasoline-range hydrocarbons over nanostructured ZSM-5 - Lee, Damin; Kim, Jong Jin; Ali, Mansoor; Choung, Jin Woo; Lee, Won Bo; Bae, Jong Wook; Park, Myung June (Catalysis Science and Technology, 2022)
A new kinetic model for the synthesis of gasoline-range hydrocarbons from dimethyl ether over a nanostructured ZSM-5 catalyst was developed based on the dual-cycle reaction mechanism. The production of individual olefin species was described by two independent cycles (olefinic and aromatic), and the model included surface methoxy as an intermediate in the heterogeneous reaction processes. Kinetic parameters for the model were estimated by fitting the experimental data under various conditions in the temperature range of 513-533 K, a space velocity of 2200-10 000 L kgcat−1 h−1, and a pressure of 1-5 bar, using the genetic algorithm. The developed model described the experimental results with a relative error below 15%, and the estimated kinetic parameters explained the governing behaviors of the reaction. The activation energies of olefinic methylation decreased with increasing chain length, and ethylene was more selectively produced by aromatic cracking, while the olefinic cycle was the main contributor for the production of propylene, in comparison with the aromatic cycle. With the developed model, the dependence of product selectivity on the operating conditions (temperature and pressure) and the evolution of product yields for each species in the reactor could be predicted accurately and precisely.
Keywords: Catalytic conversion; Developed model; Gasoline-range hydrocarbons; Kinetic models; Kinetics parameter; Mechanistic kinetic models; Methoxy; Nano-structured; Reaction mechanism; ZSM-5 catalysts